Risk Assessment of Nitrofurans in Armenian Honey - Beglaryan, Meline; Pipoyan, Davit; Chirkova, Victoria (ՀՀ ԳԱԱ)
The development of the country and care for its population, along with the growing demand for Armenian honey abroad, require compliance with increasingly stringent safety and quality standards for this product. Based on the detection of residues of contaminants in Armenian honey, researchers from CENS are concerned about the potential risk to consumers. Besides the health risk to consumers, the presence of contaminations in honey could have a negative impact on the export of the product and its contribution to the country’s economy. The article analyzed data from tested samples of Armenian honey for the presence of nitrofuran metabolite residues. According to the test results, out of the four metabolites, only one metabolite, 1-aminoguanidine (AHD), was detected in the honey samples. To assess the risk, the Margin of Exposure (MOE) method and the formation of homogeneous consumer clusters were used, considering different daily honey consumption levels and gender of consumers. Also, the worst-case scenario was considered, simulating an increase in the daily consumption of honey with a maximum concentration of AHD. The results showed safe MOE values for all consumer groups, indicating no concerns associated with nitrofuran exposure. Moreover, the worst-case scenario demonstrates the possibility of increasing the daily consumption of honey without harmful effects on the consumers. Nevertheless, the presence of contaminant in honey is a cause for concern. Երկրի զարգացումը եւ նրա բնակչության նկատմամբ մտահոգությունը, ինչպես նաեւ արտերկրում հայկական մեղրի աճող պահանջարկը ստիպում են պահպանել այս արտադրանքի անվտանգության եւ որակի ավելի խիստ պահանջները: Հայկական մեղրի մեջ աղտոտիչների մնացորդային քանակությունների հայտնաբերման դեպքերով պայմանավորված՝ հետազոտողները մտահոգված են սպառողների համար հնարավոր ռիսկի առկայությամբ։ Բացի սպառողների առողջության համար վտանգից, մեղրի մեջ աղտոտիչների առկայությունը կարող է բացասաբար ազդել արտադրանքի արտահանման եւ երկրի տնտեսության մեջ դրա ներդրման վրա: Развитие страны и забота о ее населении, а также растущий спрос на армянский мёд за рубежом вызывают необходимость соответствия всё более строгим требованиям безопасности и качества этого продукта. На основании случаев обнаружения остатков загрязняющих веществ в армянском мёде исследователи обеспокоены возможным наличием риска для потребителей. Кроме риска здоровью потребителей, наличие контаминаций в мёде может негативно сказаться на экспорте продукта и его вкладе в экономику страны.
Keywords: Natural Sciences; Food safety